A PANEL ANALYSIS OF THE STOCK RETURN–DIVIDEND YIELD RELATION: PREDICTING RETURNS AND DIVIDEND GROWTH*. (9th April 2012) - MCMILLAN, DAVID G.; WOHAR, MARK E.
<x xml:space="preserve">Abstract</x> We investigate dividend yield predictability for stock returns and dividend growth for eight countries over the period 1973–2010. We employ panel methods and report evidence of such predictive power over the full sample. An examination by decade reveals that the predictive ability for stock returns and dividend growth varies with time. Indeed, the strength of this predictability switches between returns and dividend growth. In the 1970s only returns were predicted, while in the 1980s only dividend growth was predicted. In the 1990s and 2000s, both variables were predicted, although the coefficient magnitude and strength of the statistical relationship changes.